1996
DOI: 10.1177/036354659602400617
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Stress Fractures in Track and Field Athletes

Abstract: The aim of this 12-month prospective study was to investigate risk factors for stress fractures in a cohort of 53 female and 58 male track and field athletes, aged 17 to 26 years. Total bone mineral content, regional bone density, and soft tissue composition were measured using dual-energy x-ray absorptiometry and anthropometric techniques. Menstrual characteristics, current dietary intake, and training were assessed using questionnaires. A clinical biomechanical assessment was performed by a physical therapis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
327
10
9

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 440 publications
(362 citation statements)
references
References 43 publications
16
327
10
9
Order By: Relevance
“…Previous studies have reported lower lumbar spine BMD in amenorrheic than eumenorrheic athletes (13,(34)(35)(36).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies have reported lower lumbar spine BMD in amenorrheic than eumenorrheic athletes (13,(34)(35)(36).…”
Section: Discussionmentioning
confidence: 92%
“…Exercise has previously been shown to enhance the bone's accrual on the periosteal (outer) bone surface, thus conferring greater resistance to bending, whereas estrogen may inhibit periosteal apposition (12). In eumenorrheic women, exercise may be a potential preventive measure for osteoporotic fractures, as the increased high impact loads can lead to increases in BMD relative to sedentary women (13,14). However in amenorrheic athletes, estrogen deficiency is related to bone loss, raising concerns about increased risk of future osteoporosis (11,12).…”
mentioning
confidence: 99%
“…Basketball athletes have a prominence of the medial malleolus, navicular bone and metatarsal stress fractures, while for footballers lesser metatarsal fractures are more common. 6,7,8 From a biomechanical point of view, fatigue fractures are the result of specific, cyclical and repetitive muscle action until exhaustion, with load transfer to the bone exceeding its adaptation capacity. 8,10 The shear and compression forces stimulate bone transformation according to Wolff's law, that is, the compression forces promote osteoblast activity and bone deposition leading to a strengthening of bone structures, adapting to the applied load, while shear forces lead to the reverse process of bone resorption by stimulating osteoclast activity.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…22 The same occurs with age: older individuals present a higher incidence of such fractures (B). 7 Stress fractures are less common in children than adolescents and adults (D). 23 In relation to sex, some studies have shown that military women have an incidence 5 to 10 times higher than men (B).…”
Section: Fractures?mentioning
confidence: 99%
See 1 more Smart Citation